2022
DOI: 10.3389/fpsyg.2022.950387
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Game of Post-conflict Management for New Generation of Construction Workers in China: The Mediating Role of Foremen

Abstract: The emotional perception of the new generation of Chinese construction workers is becoming stronger, and the traditional punishment-type management model is gradually failing. In order to address the safety hazards caused by the negative emotions generated after workers' conflict events, the motivation of workers to actively participate in the construction of safety climate is increased, and the safety performance of construction projects is enhanced. This paper introduces emotional event theory to assess work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“… r Moral identity coefficient: the negative impact of unsafe behaviour on work engagement. The higher the value, the stronger the guilt about the rule-breaking behaviour 49 . Rule variables R Negative impact on safety responsibility: China’s Regulations on the Management of Construction Work Safety stipulate that all parties involved in the construction have supervisory responsibilities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… r Moral identity coefficient: the negative impact of unsafe behaviour on work engagement. The higher the value, the stronger the guilt about the rule-breaking behaviour 49 . Rule variables R Negative impact on safety responsibility: China’s Regulations on the Management of Construction Work Safety stipulate that all parties involved in the construction have supervisory responsibilities.…”
Section: Methodsmentioning
confidence: 99%
“…The evolutionary game model proposed in literatures 41 , 49 , 51 were utilized to conduct various perspectives of optimization analysis on the implementation pathway of safety performance in the construction industry. There exists a typical 2-player, 2 2 game model, as well as an extended 3-player, 3 3 game model with 8 strategy sets.…”
Section: Methodsmentioning
confidence: 99%
“…For a long time, labor subcontractors have been the most indispensable party in construction projects, but they have to follow the direction of constructors and investors in terms of project decision-making. With the spread of education for all in China and the standardization of the construction industry, the quality of China’s construction workers has further improved and their individuality and construction involvement have been met [ 28 ], giving them a place in project decision-making.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al [44] confirmed the moderating role of psychological capital in the impact of safety stress on safe behavior, suggesting that the adverse effects of safety stress on safe behavior can be mitigated through the adjustment of psychological capital. Progress has also been made in the research on the design of management strategies, where Peng et al [79] introduced an evolutionary game model to compare the differences in behavioral evolution under various management strategies, thereby providing recommendations for the implementation of management strategies in diverse contexts.…”
Section: Interventions For Cwsrbmentioning
confidence: 99%